Mark Twain, travel books, and tourism : the tide of a great popular movement - Melton, Jeffrey Alan, 1962- (Studies in American literary realism and naturalism., 2002)
This illuminating study reevaluates an often overlooked aspect of Mark Twain's writing-his travel narratives-and demonstrates their centrality to his identity and thinking. Travel books, Jeffrey Melton asserts in this study, are vital to Mark Twain's identity as a writer and to his cultural influence, and not just, as many critics have argued, preliminary sketches or failed attempts at fiction. Furthermore, the identity that Twain establishes for himself in these books as the arch "tourist" provides the most compelling perspective from which to view his entire body of work. Melton be